PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA DEPARTEMEN NETWORK MONITORING CENTER PT PASIFIK SATELIT NUSANTARA - Nafila; Fajar Cahyo Utomo (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2017)
The aims of this study is to analyze the influence of leadership style and motivation on employee performance. The sample used is a saturated sample, which makes all employees (40 people in total) are respondents. The result of this study proves that leadership style has an effect on employee performance, it indicates that there are 4 (four) indicators on leadership style that must be maintained which is (1) Credible leader in managing the organization's future, (2) Committed to wages for the good performance on subordinates, (3) Realistically assessing the environmental constraints, and (4) Understand the ability of subordinates. Motivation also affects employee performance, where there are also 3 (three) maintained indicators which is (1) The leader provides real guidance according to work standards, (ii) Providing adequate working facilities and (3) comfortable working atmosphere.